Wnt/β-catenin signaling pathway: proteins' roles in osteoporosis and cancer diseases and the regulatory effects of natural compounds on osteoporosis - Xiaohao Wang; Zechao Qu; Songchuan Zhao; Lei luo; Liang Yan (BMC, 2024)
Abstract Osteoblasts are mainly derived from mesenchymal stem cells in the bone marrow. These stem cells can differentiate into osteoblasts, which have the functions of secreting bone matrix, promoting bone formation, and participating in bone remodeling. The abnormality of osteoblasts can cause a variety of bone-related diseases, including osteoporosis, delayed fracture healing, and skeletal deformities. In recent years, with the side effects caused by the application of PTH drugs, biphosphonate drugs, and calmodulin drugs, people have carried out more in-depth research on the mechanism of osteoblast differentiation, and are actively looking for natural compounds for the treatment of osteoporosis. The Wnt/β-catenin signaling pathway is considered to be one of the important pathways of osteoblast differentiation, and has become an important target for the treatment of osteoporosis. The Wnt/β-catenin signaling pathway, whether its activation is enhanced or its expression is weakened, will cause a variety of diseases including tumors. This review will summarize the effect of Wnt/β-catenin signaling pathway on osteoblast differentiation and the correlation between the related proteins in the pathway and human diseases. At the same time, the latest research progress of natural compounds targeting Wnt/β-catenin signaling pathway against osteoporosis is summarized.